Semiconductor manufacturing apparatus component
Patent Information
- Application Number
- CN202280020196.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-03-30
- Filing Date
- 2022-10-14
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2042-10-14
Smart Images

Figure CN117157744B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to components for semiconductor manufacturing apparatus. Background Technology
[0002] Conventionally, components for semiconductor manufacturing apparatuses include an AlN ceramic substrate with multiple small protrusions on its surface and a resistive heating element embedded in the AlN ceramic substrate. A wafer is placed on the surface of the AlN ceramic substrate in contact with the multiple small protrusions. It is necessary to minimize the introduction of impurities into the wafer placed on the AlN ceramic substrate. Considering this, Patent Document 1 proposes a method with multiple laser marks extending linearly along the sides of the small protrusions. This prevents the generation of microparticles due to the shedding of crystal particles from the small protrusions.
[0003] Existing technical documents
[0004] Patent documents
[0005] Patent Document 1: Japanese Patent No. 6960260 Summary of the Invention
[0006] The problem that the invention aims to solve
[0007] However, in Patent Document 1, since the laser marks extending linearly on the side of the small protrusion become so-called slag (a part formed by the solidification of temporarily molten material), the slag may be the cause of the generation of particles.
[0008] This invention was made to solve such a problem, and its main purpose is to effectively prevent the generation of particulate matter.
[0009] Methods for solving problems
[0010] [1] The semiconductor manufacturing apparatus component of the present invention is a semiconductor manufacturing apparatus component having a wafer-carrying protrusion provided on the surface of an AlN ceramic substrate.
[0011] At least a portion of the AlN ceramic matrix without the protrusions has a surface region extending from the surface to a predetermined depth and a base material region located below the surface region. The predetermined depth is 5 μm or less, and the oxygen content of the surface region is higher than the oxygen content of the base material region.
[0012] In this component for a semiconductor manufacturing apparatus, the oxygen content in the surface region is higher than that in the base material region. As a result, the surface region, in which at least a portion of the unprotruding portion of the AlN ceramic substrate is located, becomes harder than the base material region. Therefore, the generation of particulate matter can be effectively prevented during wafer processing.
[0013] [2] In the above-described semiconductor manufacturing apparatus component (the semiconductor manufacturing apparatus component described in [1] above), it is preferable that the oxygen content of the surface region is 2.0 times or more the oxygen content of the base material region.
[0014] [3] In the semiconductor manufacturing apparatus component described above (the semiconductor manufacturing apparatus component described in [1] or [2] above), it is preferable that the surface region is blackened. In this way, the surface region easily absorbs heat and therefore easily releases radiant heat. Therefore, it is easy to make the wafer temperature uniform.
[0015] [4] In the semiconductor manufacturing apparatus component described above (the semiconductor manufacturing apparatus component described in any one of [1] to [3] above), it is preferable that no slag is visible in the surface region. In this way, since no slag that may be a cause of particulate matter is visible, the generation of particulate matter can be prevented more effectively.
[0016] [5] In the semiconductor manufacturing apparatus component described above (the semiconductor manufacturing apparatus component described in any one of [1] to [4] above), it is preferable that the mass ratio O / N of the surface region is greater than the mass ratio O / N of the base material region.
[0017] [6] In the above-described semiconductor manufacturing apparatus component (the semiconductor manufacturing apparatus component described in [5] above), it is more preferable that the mass ratio O / N of the surface region is 2.2 times or more of the mass ratio O / N of the base material region.
[0018] [7] In the semiconductor manufacturing apparatus component described above (the semiconductor manufacturing apparatus component described in any one of [1] to [6] above), it is preferable that the mass ratio Al / N of the surface region is greater than the mass ratio Al / N of the base material region.
[0019] [8] In the semiconductor manufacturing apparatus component described above (the semiconductor manufacturing apparatus component described in any one of [1] to [7] above), the portion of the AlN ceramic substrate in which the protrusion is not provided may also have the surface region and the base material region described above. Attached Figure Description
[0020] Figure 1 This is a top view of the AlN heater 10.
[0021] Figure 2 yes Figure 1 AA section diagram.
[0022] Figure 3 This is a manufacturing process diagram of the AlN heater 10.
[0023] Figure 4 This is a manufacturing process diagram of the AlN heater 10.
[0024] Figure 5 This is a manufacturing process diagram of the AlN heater 10.
[0025] Figure 6 This is an enlarged image of the cross-section of the AlN ceramic matrix from Example 1.
[0026] Figure 7 This is an enlarged image of the cross-section of the AlN ceramic matrix from Example 2. Detailed Implementation
[0027] Hereinafter, preferred embodiments of the present invention will be described with reference to the accompanying drawings. Figure 1 This is a top view of the AlN heater 10. Figure 2 yes Figure 1 AA section diagram.
[0028] In the following explanation, "up" and "down" do not indicate an absolute positional relationship, but rather a relative one. Therefore, depending on the orientation of the AlN heater 10, "up" and "down" will become "down" and "up," or "left" and "right," or "front" and "back." Furthermore, the "~" indicating a numerical range means that the values recorded before and after it are included as the lower and upper limits.
[0029] The AlN heater 10 of this embodiment is an example of a component for a semiconductor manufacturing apparatus of the present invention. It has protrusions (small protrusions 14 and sealing strips 15) for wafer placement on the surface of the AlN ceramic substrate 12, and electrodes 16 are provided inside the AlN ceramic substrate 12.
[0030] The AlN ceramic matrix 12 is a circular sintered body with AlN as the main component. The dimensions of the AlN ceramic matrix 12 are, for example, a diameter of 200–450 mm and a thickness of 10–30 mm. In addition to AlN, the AlN ceramic matrix 12 may also contain components derived from sintering aids. Examples of sintering aids for AlN include rare earth metal oxides. Examples of rare earth metal oxides include Y₂O₃ and Yb₂O₃. It should be noted that "main component" refers to a component that accounts for 50% or more by volume (preferably 70% or more by volume, more preferably 85% or more by volume) or the component with the highest volume proportion among all components (the same applies below).
[0031] The small protrusions 14 are multiple flat cylindrical protrusions spaced apart on the entire surface of the AlN ceramic substrate 12. The dimensions of the small protrusions 14 are, for example, a diameter of 0.5 to 3 mm and a height of 10 to 50 μm.
[0032] The sealing strip 15 is an annular protrusion formed along the outer edge of the AlN ceramic substrate 12 on its surface. The sealing strip 15 is arranged to surround a plurality of small protrusions 14. The height of the sealing strip 15 is the same as the height of the small protrusions 14.
[0033] Electrode 16 is disposed inside AlN ceramic substrate 12 in a manner parallel to the surface of AlN ceramic substrate 12. In this embodiment, electrode 16 is a heater electrode. The heater electrode is an electrode formed by wiring a resistive heating element from one end to the other in a single stroke, covering the entire AlN ceramic substrate 12 when viewed from above. Examples of materials for electrode 16 include high-melting-point metals such as W and Mo, or their carbides. It should be noted that "parallel" means not only perfectly parallel, but also, even if not perfectly parallel, is considered parallel as long as it is within the allowable error range (tolerance, etc.) (the same applies below).
[0034] The portion 12A of the AlN ceramic matrix 12 without protrusions (small protrusions 14 and sealing strips 15) has a surface region 12Aa extending from the surface to a predetermined depth and a base material region 12Ab located below the surface region 12Aa. The predetermined depth is 5 μm or less (preferably 0.1 to 2.0 μm). The oxygen content of the surface region 12Aa is preferably 2.0 times or more than the oxygen content of the base material region 12Ab, more preferably 2.9 times or more. The surface region 12Aa is preferably blackened. It is preferable that no slag is visible in the surface region 12Aa. The mass ratio O / N of the surface region 12Aa is preferably greater than the mass ratio O / N of the base material region 12Ab, more preferably 2.2 times or more, and even more preferably 3.6 times or more. The mass ratio of surface region 12Aa to Al / N is preferably greater than that of the mass ratio of parent material region 12Ab to Al / N, more preferably 1.1 times or more, and even more preferably 1.2 times or more.
[0035] Next, an example of using the AlN heater 10 will be described. First, the AlN heater 10 is placed in a chamber (not shown). Then, a wafer is placed on the surface of the AlN heater 10. The wafer is supported by the top surfaces of the plurality of small protrusions 14 and the top surface of the sealing strip 15. Then, an external heater power supply is connected to the electrode 16, which serves as the heater electrode, so that current flows through the electrode 16. As a result, the electrode 16 heats up, heating the wafer to a predetermined temperature. In the space surrounded by the surface region 12Aa, the plurality of small protrusions 14, the sealing strip 15, and the wafer, a heat-conducting gas (e.g., He gas) is supplied from a gas passage (not shown) that runs vertically through the AlN heater 10. Various processes are performed on the wafer in this state. After the processing is completed, the power supply to the electrode 16 is turned off, and the wafer is removed from the surface of the AlN heater 10.
[0036] Next, a manufacturing example of the AlN heater 10 will be described. Figure 3 This is a manufacturing process diagram of the AlN heater 10. First, a circular AlN ceramic sintered body 21 is prepared. Electrode paste is then printed on the upper surface of the AlN ceramic sintered body 21 in a manner that forms a predetermined electrode pattern to form a heating electrode precursor 26. Figure 3 A). The electrode paste is prepared by adding organic solvents and binders to a mixture of electrode material powder and AlN powder, and then mixing and kneading it. Next, a laminate 23 is formed by stacking circular AlN ceramic molded bodies 22 to cover the heater electrode precursor 26. Figure 3 B). Then, by hot pressing and sintering the laminate 23, the heater electrode precursor 26 is sintered to become the electrode 16 (heater electrode), and the AlN ceramic sintered body 21 sandwiched between the heater electrode precursor 26 and the AlN ceramic molded body 22 is sintered to become an integral AlN ceramic structure 24. Figure 3 C).
[0037] Next, the surface of the AlN ceramic structure 24 is polished to a mirror finish. Then, ablation is performed on the surface outside the areas where the small protrusions 14 and sealing strips 15 are formed by scanning with a short-pulse laser. This forms multiple small protrusions 14 and sealing strips 15 on the surface of the AlN ceramic structure 24. As a result, the AlN ceramic structure 24 becomes the AlN ceramic substrate 12, yielding the AlN heater 10. Figure 3 D). The top surfaces of the small protrusions 14 and the sealing strip 15 maintain a mirror-like state. During ablation, material is removed by breaking interatomic bonds, and the removed material undergoes a change in crystal structure and is thus modified. As a result, the oxygen content of the surface region 12Aa becomes more than 2.0 times that of the parent material region 12Ab, or the mass ratio of O / N and Al / N of the surface region 12Aa becomes a value greater than that of the parent material region 12Ab. The pulse width of the short-pulse laser is preferably in the nanosecond range or below (picosecond or femtosecond range). During ablation, the surface subjected to laser processing becomes harder due to modification, thus suppressing the generation of microparticles and making the surface black. In addition, during ablation, the formation of slag, which is the cause of microparticle formation, is suppressed, thus suppressing microparticle formation compared to the case where slag is formed. Furthermore, during the ablation process, only the portion that absorbed the laser is removed, thus reducing the thermal impact on the small protrusion 14 and the sealing strip 15, allowing the edges of the small protrusion 14 and the sealing strip 15 to be approximately perpendicular. Therefore, even if the small protrusion 14 and the sealing strip 15 wear down, their contact area with the wafer can be maintained at a constant level.
[0038] In the AlN heater 10 of this embodiment described above, the oxygen content of the surface region 12Aa, where no protrusions (small protrusions 14 and sealing strips 15) are provided on the surface of the AlN ceramic substrate 12, is more than 2.0 times that of the oxygen content of the base material region 12Ab. As a result, the surface region 12Aa is harder than the base material region 12Ab. Therefore, the generation of particulate matter can be effectively prevented during wafer processing.
[0039] Furthermore, the surface region 12Aa is preferably blackened. This allows the surface region 12Aa to easily absorb heat and thus easily release radiant heat. Therefore, it facilitates uniform wafer temperature.
[0040] Furthermore, it is preferable that no residue is visible in the surface region 12Aa. In this way, residue that could potentially cause particulate formation is not visible, thus more effectively preventing particulate formation.
[0041] Furthermore, the mass ratio O / N of the surface region 12Aa is preferably greater than that of the base material region 12Ab, and more preferably 2.2 times or more. The mass ratio Al / N of the surface region 12Aa is preferably greater than that of the base material region 12Ab.
[0042] It should be noted that the present invention is not limited to the above-described embodiments. As long as it falls within the technical scope of the present invention, it can be implemented in various ways.
[0043] In the above embodiments, a heater electrode as electrode 16 is illustrated by being built into the AlN ceramic substrate 12, but this is not particularly limiting. For example, an electrostatic electrode or an RF electrode may be built into the electrode 16. In addition, an electrostatic electrode and / or an RF electrode may be built into the heater electrode.
[0044] In the above embodiment, the surface of the AlN ceramic structure 24 is polished to a mirror finish, and then ablation is performed on the surface except for the areas where protrusions (small protrusions 14 and sealing strips 15) are formed by scanning a short-pulse laser. However, this is not a limitation. For example, after fabricating the AlN ceramic structure 24 and before polishing its surface, ablation can be performed on the areas except for the areas where protrusions are formed by scanning a short-pulse laser to form protrusions, and then the surface of the protrusions can be polished to a mirror finish. Alternatively, instead of forming protrusions solely by laser, other processing methods such as sandblasting can be combined with laser processing. For example, after fabricating the AlN ceramic structure 24, such as... Figure 4As shown in Figure A, small protrusions 14 and sealing strips 15 are formed by grinding areas on the surface other than the areas that form protrusions through sandblasting (a process in which abrasive material is impacted onto the surface). Figure 4 B), the ground area is irradiated with a laser to modify the area and form a surface region 12Aa, thereby obtaining an AlN heater 10. Figure 4 C). Additionally, if modification of the top and / or sides of the protrusion is also required, laser irradiation can be applied to the top and / or sides of the protrusion. For example, short-pulse laser scanning can be used to ablate the top and sides of the small protrusion 14 of the AlN heater 10 and the sealing strip 15. Figure 5 A) A surface region 12Aa is formed on the entire surface of the AlN heater 10, including the top and side surfaces containing the small protrusions 14 and the sealing strip 15. Figure 5 B). In this case, it is preferable to adjust the laser output power in a manner that does not cause the protrusion to disappear.
[0045] In the above-described embodiments, the portion 12A of the AlN ceramic matrix 12 without protrusions (small protrusions 14 and sealing strips 15) has a surface region 12Aa and a base material region 12Ab, but is not particularly limited thereto. For example, a portion of portion 12A may also have a surface region 12Aa and a base material region 12Ab. Such a structure is also included within the scope of the present invention. Thus, as long as at least a portion of the portion 12A without protrusions has a surface region 12Aa and a base material region 12Ab, it is included within the scope of the present invention; therefore, the protruding portion may or may not have a surface region 12Aa and a base material region 12Ab. For example, at least a portion of the top surface of the protrusion may have a surface region 12Aa and a base material region 12Ab, or the top surface of the protrusion may not have a surface region 12Aa and a base material region 12Ab. In addition, at least a portion of the side of the protrusion may have a surface region 12Aa and a base material region 12Ab, or the side of the protrusion may not have a surface region 12Aa and a base material region 12Ab.
[0046] Example
[0047] The embodiments of the present invention will be described below. It should be noted that the following embodiments do not limit the present invention.
[0048] [Reference Example 1]
[0049] The following describes the fabrication of a disc-shaped AlN ceramic matrix (base material A, diameter 320 mm, thickness 20 mm) without internal electrodes. First, 100 parts by weight of aluminum nitride powder (99.7% purity), 5 parts by weight of yttrium oxide, 2 parts by weight of dispersant (polycarboxylic acid copolymer), and 30 parts by weight of dispersion medium (polyester) are mixed for 14 hours using a ball mill (drum sieve) to obtain a ceramic slurry precursor. Then, relative to this ceramic slurry precursor, 4.5 parts by weight of isocyanate (4,4'-diphenylmethane diisocyanate), 0.1 parts by weight of water, and 0.4 parts by weight of catalyst (6-dimethylamino-1-hexanol) are added and mixed to obtain a ceramic slurry. This ceramic slurry is then poured into a molding die with a disc-shaped internal space. After the isocyanate and water react chemically to form an organic binder (polyurethane resin), the cured molded body is removed from the molding die. The molded body was dried at 100℃ for 10 hours, then degreased and calcined at a maximum temperature of 1300℃ under a hydrogen atmosphere to obtain a calcined ceramic body. The calcined ceramic body was then subjected to a nitrogen atmosphere and a pressing pressure of 250 kgf / cm². 2 AlN ceramic matrices were prepared by hot-pressing at 1860℃ for 6 hours. The mass percentages of N, O, Al, and Y in the obtained AlN ceramic matrix were determined by EDX analysis. Additionally, the color of the AlN ceramic matrix was visually determined, and the hardness was measured using a Mitutoyo HM-211 micro Vickers hardness tester. These results are shown in Table 1.
[0050] [Example 1]
[0051] The surface of substrate A was ablated using a picosecond laser ablation machine. The picosecond laser ablation machine scanned the substrate surface in parallel at 5 μm intervals, simultaneously driving the motors of the galvanometer reflector and the stage. The processing wavelength, scanning speed, pulse width, and laser output power were set to the values shown in Table 1, and the frequency was set to 200 kHz. The ablation was performed twice. After processing, the cross-section of the AlN ceramic substrate was examined, resulting in a surface region (the area from the surface blackened to 0.5 μm) and the substrate region below this surface region. For the surface region, the mass percentages of N, O, Al, and Y were calculated, similar to those for substrate A. Furthermore, the ratio of oxygen content in the surface region to that in the substrate region, the O / N mass ratio in the surface region to that in the substrate region, and the Al / N mass ratio in the surface region to that in the substrate region were calculated. The color and hardness of the surface region were then measured, similar to those for substrate A. These results are shown in Table 1. The surface region has a hardness of 670 Hv, which is approximately 1.28 times that of the base material region (523 Hv). Thus, the surface region of Example 1 is harder than the base material A (Reference Example 1), thereby improving the particle suppression effect compared to base material A. Furthermore, scanning electron microscopy (SEM) observation of the surface region of Example 1 revealed no residue. Therefore, the particle suppression effect is improved compared to Patent Document 1.
[0052] [Reference Example 2]
[0053] A circular AlN ceramic matrix (base material B) with the same dimensions as base material A was prepared using the same method. For the resulting AlN ceramic matrix, the mass percentages of N, O, Al, and Y were calculated in the same manner as for base material A. Since base material B was from a different batch than base material A, the mass percentages of the elements differed. Additionally, the color and hardness of the AlN ceramic matrix were measured in the same manner as for base material A. These results are shown in Table 1.
[0054] [Examples 2-4]
[0055] The surface of the substrate B was ablated using a nanosecond laser processing machine. The nanosecond laser processing machine, while driving the motors of the galvanometer mirror and the stage, scanned the substrate surface in parallel at 5μm intervals to perform the ablation. In Examples 2 to 4, the processing wavelength, scanning speed, pulse width, and laser output power were set to the values shown in Table 1, the frequency was set to 50kHz, and the number of processing cycles was set to 1. After processing, the cross-section of the AlN ceramic substrate was inspected, resulting in a surface region and the substrate region below the surface region. The surface region in Example 2 was from the surface to 0.2μm, the surface region in Example 3 was from the surface to 0.3μm, and the surface region in Example 4 was from the surface to 0.2μm. For each surface region in Examples 2 to 4, the mass percentages of N, O, Al, and Y were calculated in the same manner as for the substrate A. Furthermore, the ratio of oxygen content in the surface region to oxygen content in the parent material region, the ratio of the surface region's O / N mass ratio to the parent material's O / N mass ratio, and the ratio of the surface region's Al / N mass ratio to the parent material's Al / N mass ratio were determined. Then, the color and hardness of the surface region were measured in the same manner as with parent material A. These results are shown in Table 1. The hardness of the surface region was 650–690 Hv, approximately 1.16–1.23 times that of the parent material region (560 Hv). Thus, the hardness of each surface region in Examples 2–4 became harder than that of parent material B (Reference Example 2), thereby improving the particle suppression effect compared to parent material B. Furthermore, the surface regions of Examples 2–4 were observed using a scanning electron microscope (SEM), and no residue was observed. Therefore, the particle suppression effect was improved compared to Patent Document 1.
[0056] [Reference Example 3]
[0057] A circular AlN ceramic matrix (base material C) with the same dimensions as base material A was prepared using the same method. For the resulting AlN ceramic matrix, the mass percentages of N, O, Al, and Y were calculated in the same manner as for base material A. Since base material C was from a different batch than base material A, the mass percentages of the elements differed. Additionally, the color and hardness of the AlN ceramic matrix were measured in the same manner as for base material A. These results are shown in Table 1.
[0058] [Examples 5 and 6]
[0059] The surface of the substrate C was ablated using a picosecond laser processing machine. The picosecond laser processing machine, while driving the motors of the galvanometer reflector and the stage, scanned the substrate surface in parallel at 5μm intervals to perform the ablation. In Examples 5 and 6, the processing wavelength, scanning speed, pulse width, and laser output power were set to the values shown in Table 1, the frequency was set to 200kHz, and the number of processing cycles was set to 1. After processing, the cross-section of the AlN ceramic substrate was inspected, resulting in a surface region and the substrate region below the surface region. The surface regions in Examples 5 and 6 were all regions extending from the surface to 0.5μm. For each surface region in Examples 5 and 6, the mass percentages of N, O, Al, and Y were calculated in the same manner as for the substrate A. Furthermore, the ratio of oxygen content in the surface region to oxygen content in the substrate region, the ratio of the surface region's O / N mass ratio to the substrate region's O / N mass ratio, and the ratio of the surface region's Al / N mass ratio to the substrate region's Al / N mass ratio were calculated. Furthermore, the color and hardness of the surface region were measured in the same manner as with the base material A. These results are shown in Table 1. The hardness of the surface region ranged from 459.9 to 635.9 Hv, approximately 1.11 to 1.54 times that of the base material region (413 Hv). Thus, the hardness of each surface region in Examples 5 and 6 became harder than that of the base material C, thereby improving the particle suppression effect compared to the base material C. Additionally, scanning electron microscopy (SEM) was used to observe each surface region in Examples 5 and 6, and no residue was observed. Therefore, the particle suppression effect was improved compared to Patent Document 1.
[0060] [Table 1]
[0061]
[0062] Figure 6 This is an enlarged image of the cross-section of the AlN ceramic matrix from Example 1. Figure 7 This is a magnified image of the cross-section of the AlN ceramic matrix from Example 2. Figure 6 and Figure 7 In the figure, the length of the entire scale (10 scale units) is 1.00 μm.
[0063] This application claims priority based on Japanese Patent Application No. 2022-055112, filed on March 30, 2022, the entire contents of which are incorporated herein by reference.
[0064] Industrial availability
[0065] The present invention can be used as a component in semiconductor manufacturing apparatus such as a wafer processing apparatus for processing wafers.
[0066] Symbol Explanation
[0067] 10: AlN heater, 12: AlN ceramic matrix, 12A: part without protrusions, 12Aa: surface area, 12Ab: base material area, 14: small protrusion, 15: sealing strip, 16: electrode, 21: AlN ceramic sintered body, 22: AlN ceramic molded body, 23: laminate, 24: AlN ceramic structure, 26: heating electrode precursor.
Claims
1. A component for a semiconductor manufacturing apparatus, wherein a wafer-mounting protrusion is provided on the surface of an AlN ceramic substrate, wherein, At least a portion of the AlN ceramic matrix without the protrusions has a surface region extending from the surface to a predetermined depth and a base material region located below the surface region, the predetermined depth being less than 5 μm, and the oxygen content of the surface region being higher than the oxygen content of the base material region. The mass ratio O / N of the surface region is a larger value than the mass ratio O / N of the base material region.
2. The component for a semiconductor manufacturing apparatus according to claim 1, wherein, The oxygen content of the surface region is more than 2.0 times that of the oxygen content of the base material region.
3. The component for a semiconductor manufacturing apparatus according to claim 1 or 2, wherein, The surface area is blackened.
4. The component for a semiconductor manufacturing apparatus according to claim 1 or 2, wherein, No residue is visible in the surface area.
5. The component for a semiconductor manufacturing apparatus according to claim 1 or 2, wherein, The mass ratio O / N of the surface region is more than 2.2 times that of the mass ratio O / N of the base material region.
6. The component for a semiconductor manufacturing apparatus according to claim 1 or 2, wherein, The mass ratio Al / N of the surface region is greater than that of the mass ratio Al / N of the base material region.
7. The component for a semiconductor manufacturing apparatus according to claim 1 or 2, wherein, The portion of the AlN ceramic matrix without the protrusions has the surface region and the base material region.
Citation Information
Patent Citations
Electric power conversion system
JP2022055112A
Mounting member and manufacturing method thereof
JP2012119378A
Substrate holding device and manufacturing method thereof
JP6960260B2
